Recycling efficiency optimization of tungsten-filled Vinyl-Methyl-Silicone-based flexible gamma ray shielding materials - Tao Wu; Jie Wang; Qiuyu Sun; Yifan Yang; Qingyu Si; Chenyu Liang; Guoming Liu; Aijun Mi; Sheng Wang (Nuclear Engineering and Technology)
Tungsten has been widely used for gamma-ray and X-ray radiation shielding, which is one of the main elements of shielding materials. Compared with traditional lead-containing shielding materials, tungsten-containing shielding materials have several advantages, such as good chemical stability, a high melting point and relative environmental friendliness. Considering the recycling of resources, the optimization of pyrolysis temperature and pyrolysis duration of tungsten-filled Vinyl-Methyl-Silicone-based flexible shielding materials needs to be studied. In this paper, these tungsten-filled Vinyl-Methyl-Silicone-based flexible shielding materials were initially recycled using pyrolysis. Subsequently, the crystal structures, surface chemical states and the tungsten concentration after pyrolysis in an argon atmosphere were characterized. In order to increase the tungsten recycling rate, the pyrolyzed samples were further recycled using the ultrasonic cleaning method. Furthermore, the influence of ultrasonic cleaning on tungsten recycling rate and surface morphologies was characterized and analyzed. It is found that the tungsten recycling rate of tungsten-filled Vinyl-Methyl-Silicone based flexible gamma/X-ray shielding material was around 69.9 wt%-81.6 wt% by using the pyrolysis method, while the recycling rate of tungsten can exceed 90.0 wt% by ultrasonic cleaning after pyrolysis.